Project Finance Syndication: An Evaluation of the Challenges Faced by Parastatals in Accessing Project Finance in Developing Countries, a Case of Zambia - Francis Nyirenda; Hanson Chishimba (Global Journal of Management and Business Research, 2024)
The presence of good infrastructure and social amenities not only provides opportunities for employment and a physical beautiful environment but most importantly attracts direct foreign investments which may open a lot of doors for developing countries It is for this reason that African countries particularly parastatals in Zambia have felt the need to participate actively to build and provide good roads state of art hospitals housing telecommunications infrastructure schools and shopping malls However these parastatals face a myriad of challenges in accessing project finance Therefore this study evaluated the challenges faced by parastatals in procuring project finance Qualitative approach was used in collecting collating analyzing and integrating data The population comprised parastatal s financial regulators and utility companies and ministry of finance The sample of Thirty 30 was drawn from boards of directors officials in charge of finance investments and regulations using purposive sampling The samples were drawn using purposive sampling Data was collected using questionnaires The study found that challenges in procuring project finance by parastatals can be attributed to poor company statement of financial position high debt equity ratio challenges of the treasury in terms of lacking adequate space under the Loans and Guarantees regulations resulting into a capping on the debt ceiling of the treasury delays in obtaining Sovereign Guarantees to support the borrowing on the international financial market delays in obtaining consents from Attorney Generals abandoned projects due to failure to acquire financing and the government s inability to convince multilateral development agencies to support and or extend financial facilities for key and bankable infrastructure projects